Twórczość Zygmunta Noskowskiego w kontekście dialogu kultur – polskiej i ukraińskiej: ворчість Зигмунда Носковського в контексті діалогу культур – польської і україської - Німилович, Олександра (Musica Galiciana. Kultura muzyczna Galicji w kontekście stosunków polsko-ukraińskich, 2023)
The article is dedicated to the work of the outstanding Polish composer, conductor, violinist and pianist, teacher and musicologist, active music and public figure Zygmunt Noskowski (1846–1909). His fascinating attitude to the heritage of Ukrainian folk song and dance was emphasized. The composer’s multi-genre heritage includes many works in which Ukrainian folk song and dance became an inspiration for the author. The focus is on the work of the outstanding Ukrainian poet, writer and publicist, thinker and folklorist Ivan Franko “Polish and Russian Music” – in “Polish and Russian Music” he emphasized the perfection of form, the charm of rhythmic and melodic images in the composer’s works, direct and indirect references to folklore. Z. Noskowski visited Ukraine many times, contacted Ukrainian and Polish cultural figures, got acquainted with the song and dance folklore heritage of the Ukrainian people. The article reveals the palette of the composer’s concert activity in Ukraine (Kyiv, Lviv), the history of opera performance, some symphonic, choral, instrumental works both in the early 20th century and today. Many examples of folk music formed the basis of Z. Noskowski’s compositions, both in the original presentation and in a certain reincarnation of folk song intonation models – among such works: Ukrainian melodies on the themes of Galician songs and dances for piano 4 hands (1890), Kolomyika for piano from the opera House in the Village, Tropak (Ukrainian dance) for violin and piano, 3 pieces op. 26 (Krakowiak, Ukrainian Song and Polonaise, 1890), Song from Ukraine op. 28 no. 2 and many others. Musical and aesthetic analysis of individual compositions by Z. Noskowski is presented in the article in order to reveal the images and genres in the composer’s work related to Ukraine.